Stereoselective Synthesis of New β-Lactams from 2-(1H-Pyrrol-1-yl)-1-propen-1-one as a Novel Ketene - Babaei, Elaheh; Islami, Mohammad Reza; Kalantari, Maryam (Synlett, 2013)
New trans-β-lactams have been stereoselectively prepared by the reaction of N-pyrrolylpropanoic acid with 2-chloro-1-methylpyridinium iodide and aromatic imines in the presence of triethylamine as a base via in situ generation of methyl-2-(1H-pyrrol-1-yl)ketene as a novel heteroarylketene. The trans-β-lactam was formed either as a single isomer or as the major isomer.
Keywords: ketenes; imines; N-pyrrolylpropanoic acid; [2π + 2π] cycloaddition; β-lactams